Phenolic characterization and antioxidant capacity of alcoholic extracts from raw and boiled leaves of Cnidoscolus aconitifolius (Euphorbiaceae) - Godínez-Santillán, Rosa Iris; Chávez-Servín, Jorge Luis; García-Gasca, Teresa; Guzmán-Maldonado, Salvador Horacio (Instituto de Ecología, A.C., 2019)
Background and Aims: Cnidoscolus aconitifolius is a shrubby species that is used as an ornamental, medicinal and food plant in various parts of the world, known in Mexico as chaya. Little research has been published on its phenolic composition and antioxidant capacity. The objective of this study is to determine phenolic composition and antioxidant capacity of hydroalcoholic extracts (methanol-water and ethanol-water) in different proportions from raw and boiled C. aconitifolius leaves.Methods: Cnidoscolus aconitifolius was cultivated on the campus of the University of Querétaro (Mexico; 2014) using woody cuttings. During the summer of 2016, sampling of leaves of all the plants were carried out. Total phenolic content (TPC), total flavonoid content (TFC) and antioxidant capacity were determined in raw and boiled leaves from methanol-water (50:50 and 80:20) and ethanol-water (50:50 and 80:20) extracts. Furthermore, the phenolic compounds of each of the extracts were identified and quantified by the RP-HPLC-DAD method.Key results: Eleven phenolic compounds were identified and quantified in C. aconitifolius: gallic acid, vanillic acid, vanillin, chlorogenic acid, caffeic acid, ferulic acid, rosmarinic acid, p-coumaric acid, resveratrol, luteolin and apigenin. In general, boiled leaves showed greater antioxidant capacity than raw leaves. Differences were observed in the content of the phenolic compounds depending on the type of solvent and mixture. The 80:20 ethanol extract from boiled leaves had the higher content of polyphenols.Conclusions: The boiling of the leaves increased the content of phenolic compounds in the extracts analyzed. The results of this study indicate that chaya leaves are a rich source of natural antioxidants.